2014
DOI: 10.2147/ndt.s63776
|View full text |Cite
|
Sign up to set email alerts
|

Association of dopamine D1 receptor gene polymorphism with schizophrenia: a meta-analysis

Abstract: To date, the role of dopamine D1 receptor (DRD1) polymorphism in schizophrenia remains controversial. We carried out a meta-analysis to determine whether DRD1 polymorphism influences the risk of schizophrenia. We examined whether rs4532 and rs5326 genetic variants are related to the etiology of schizophrenia, using a meta-analysis. Relevant case-control studies were retrieved by database searching and selected according to established inclusion criteria. A total of ten studies were identified and included in o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Furthermore, polymorphisms in DRD1 have been linked to ICDs, neuropsychiatric disease, problem gambling, addiction, and cognitive functioning in non-PD populations ( 31 , 32 ). Risk variants of rs5326 have been associated with a decreased DRD1 expression, a reduced cognitive functioning in both healthy males and bipolar patients, and an increased risk of neuropsychiatric disorders, such as schizophrenia and heroin addiction ( 33 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, polymorphisms in DRD1 have been linked to ICDs, neuropsychiatric disease, problem gambling, addiction, and cognitive functioning in non-PD populations ( 31 , 32 ). Risk variants of rs5326 have been associated with a decreased DRD1 expression, a reduced cognitive functioning in both healthy males and bipolar patients, and an increased risk of neuropsychiatric disorders, such as schizophrenia and heroin addiction ( 33 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…Allele groups were defined as in (ie, inserted) and de (ie, deleted). In the dominant model, 34 , 35 the pooled OR using a random effects model was 1.083 ( P z =0.377, 95% CI =0.907–1.293) with a power of 0.154 ( Table 3 ). No association was found in subgroup analysis by ethnicity or by source of controls ( Table 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…In a random model, a pooled analysis was conducted (1,912 cases and 1,836 controls) to evaluate the relationship between genotype L/L of the 120 bp TR and schizophrenia risk ( Table 6 and Figures S8–S12). In the recessive model, 34 , 35 genotype L/L was found to be a potential risk factor for schizophrenia ( P z =0.004, OR =1.275, 95% CI =1.081–1.504) with a power of 0.959 ( Table 3 ). Findings from subgroup analysis indicated significant associations in East Asian ( P z =0.002, OR =1.317, 95% CI =1.108–1.565) and hospital-based subgroups ( P z =0.002, OR =1.319, 95% CI =1.134–1.708) ( Table 4 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In humans, two SNPs, i.e., rs4532 (A-48G) and rs5326 (G-94A), in the 5'UTR of the DRD1 gene have been identified. The associations of these SNPs with increased risks of SCZ are controversial; a meta-analysis of the SZGene database reported no association (Allen et al, 2008), but another meta-analysis of the literatures reported a weak association with the DRD1 gene variant rs5326 (Pan et al, 2014).…”
Section: Damentioning
confidence: 99%